2013
DOI: 10.1371/journal.pone.0071310
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Renal Corpuscle microRNA Expression on Epithelial-to-Mesenchymal Transition in Maternal Low Protein Diet in Adult Programmed Rats

Abstract: Prior study shows that maternal protein-restricted (LP) 16-wk-old offspring have pronounced reduction of nephron number and arterial hypertension associated with unchanged glomerular filtration rate, besides enhanced glomerular area, which may be related to glomerular hyperfiltration/overflow and which accounts for the glomerular filtration barrier breakdown and early glomerulosclerosis. In the current study, LP rats showed heavy proteinuria associated with podocyte simplification and foot process effacement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(97 citation statements)
references
References 44 publications
9
79
2
7
Order By: Relevance
“…The current study sustains a pathophysiological association between renal nerve activity, decreased renal sodium excretion, and enhanced blood pressure in maternal protein-deprived offspring model. The present data also confirmed that there was a significant reduction in the birthweight of LP male offspring compared with NP offspring [37]. This effect has been linked with a significant enhancement in arterial blood pressure beyond 7 weeks of age in LP rats relative to age-matched NP counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…The current study sustains a pathophysiological association between renal nerve activity, decreased renal sodium excretion, and enhanced blood pressure in maternal protein-deprived offspring model. The present data also confirmed that there was a significant reduction in the birthweight of LP male offspring compared with NP offspring [37]. This effect has been linked with a significant enhancement in arterial blood pressure beyond 7 weeks of age in LP rats relative to age-matched NP counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…As previously demonstrated [7,28], this higher expression of TGF-β1, a major inducer of EMT in epithelial cells [37], could be associated with decreased expression of EMT-inducing transcriptional factor [38,39,40], which in turn, upregulated fibronectin and collagen renal expression, proteins being considered mesenchymal markers. The production of interstitial matrix compounds suggests that podocytes have adapted a mesenchymal phenotype in maternal tobacco exposure offspring, which could profoundly change their functions [41,42].…”
Section: Discussionmentioning
confidence: 63%
“…These adaptations may be beneficial in the short term, but may have adverse consequences in postnatal life [1]. Fetal programming by different insults results in low birth weight and reduction in nephron number [2,3,4,5,6,7], and increases the risk for adult development of cardiovascular and renal diseases [4,5,6]. Low birth weight (LBW) is also associated with impaired renal growth, raised blood pressure and impaired renal function [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and genetic factors influence the ontogenetic development, and on adverse circumstance, eventually leading to functional and structural disorders of tissues and organs. In rats, gestational protein restriction is associated with low birthweight, fewer nephrons, and increased risk for the development of heart diseases, kidney dysfunction and metabolic syndrome in adult life [1][2][3][4][5][6][7]. We recently demonstrated that maternal low-protein (LP) intake offspring have a lower birth weight, 30% fewer nephrons, and arterial hypertension [3,4,6] when compared with age-matched, normal (NP) protein intake group.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that maternal low-protein (LP) intake offspring have a lower birth weight, 30% fewer nephrons, and arterial hypertension [3,4,6] when compared with age-matched, normal (NP) protein intake group. Additionally, water and salt balance studies have shown that hypertension in LP offspring is associated with decreased urinary sodium excretion [3][4][5][6][7][8]. The involvement of the central nervous system (CNS) in the control of blood pressure and, water and salt homeostasis has been demonstrated in several studies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%